2020
DOI: 10.1080/03007995.2020.1799771
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of pembrolizumab with axitinib as first-line treatment for advanced renal cell carcinoma

Abstract: Objective: Pembrolizumab/axitinib significantly prolonged overall survival (OS) and progression-free survival (PFS), and increased objective response rate versus sunitinib in the phase III trial KEYNOTE-426 among previously untreated patients with advanced renal cell carcinoma (RCC). This study assessed the cost-effectiveness of pembrolizumab/axitinib versus other first-line treatments of advanced RCC from a US public healthcare payer perspective. Methods: A partitioned survival model with three states (progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The administration fee was based on the 2021 CMS Physician Fee Schedule, with the duration of drug infusion based on RCTs and United States Food and Drug Administration package inserts ( Centers for Medicare & Medicaid Services, 2021 ). The overall costs associated with the management of grade 3 or 4 AEs and BSC were obtained from previous literature ( Perrin et al, 2015 ; Swallow et al, 2018 ; Wan et al, 2019 ; Bensimon et al, 2020 ; Lu et al, 2020 ; Watson et al, 2020 ; Agency for Healthcare Research and Quality, US Dept of Health and Human Services (2021) ).…”
Section: Methodsmentioning
confidence: 99%
“…The administration fee was based on the 2021 CMS Physician Fee Schedule, with the duration of drug infusion based on RCTs and United States Food and Drug Administration package inserts ( Centers for Medicare & Medicaid Services, 2021 ). The overall costs associated with the management of grade 3 or 4 AEs and BSC were obtained from previous literature ( Perrin et al, 2015 ; Swallow et al, 2018 ; Wan et al, 2019 ; Bensimon et al, 2020 ; Lu et al, 2020 ; Watson et al, 2020 ; Agency for Healthcare Research and Quality, US Dept of Health and Human Services (2021) ).…”
Section: Methodsmentioning
confidence: 99%
“…They adjusted the disutility values of AEs based on the incidence rates (49%, 65/132), duration (48%, 64/132), cycle of occurrence (36%, 48/132), and/or frequency (20%, 26/132) of AEs to calculate the effect of AEs on QALYs in the intervention and control arms. For instance, Bensimon et al [ 40 ] subtracted one-time AE-related utility decrements at the beginning of the first cycle based on treatment-specific AE risks, mean durations of AEs, and the additive disutility associated with AEs.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al 29 and Lu et al 30 did not find PA or AA to be cost-effective relative to sunitinib. In several studies, PA was reported as being cost-effective compared with NI and/or sunitinib 14,20,31,32 and NI was reported as cost-effective as sunitinib. 13 A key difference between our analyses and recent publications was the assessment of drug costs.…”
Section: Discussionmentioning
confidence: 99%